CHARACTERIZATION OF THE MAGNETIC AND GEOCHEMICAL PROPERTIES OF IRON SAND IN THE TOR RIVER, SARMI REGENCY, PAPUA - Dwi Syaifullah, Mahendra
The Tor River is a watercourse located in the Sarmi Regency, Papua. An abundant amount of iron sands can be found throughout the river. Iron sands has a huge potential for commercial use, but research on iron sands along the Tor River is still scarce, which means not many people realize the difference between it and iron sands from other locations. Therefore, this study was conducted to determine the magnetic properties and the contents of iron sands found in the Tor River. To determine the magnetic properties, the frequency-based magnetic susceptibility of the samples was measured using a susceptibilitymeter as well as the magnetic remnant saturation using a Vibrating Sample Magnetometer (VSM). In determining the content of the iron sands, geochemical analysis was carried out using the XRay Diffraction (XRD) method. Interpretation of the data obtained by these methods is then correlated with one another to determine the characteristics of iron sands found along the Tor River. Measurements of the iron sand with the size of medium sands indicates low value of magnetic susceptibility with low variations along the river compared to iron sands found in other locations. It also shows the domain of iron sands to be in the SP domain. Geochemical analysis shows that the most abundant element found in this iron sands are iron (Fe) and silicon (Si).